Uplift of symmetrical anchor plates by using grid-fixed reinforced reinforcement in cohesionless soil - Niroumand, Hamed (Chinese Ocean Engineering Society and Springer-Verlag Berlin Heidelberg, 2014)
Uplift response of symmetrical anchor plates with and without grid fixed reinforced (GFR) reinforcement was evaluated in model tests and numerical simulations by Plaxis. Many variations of reinforcement layers were used to reinforce the sandy soil over symmetrical anchor plates. In the current research, different factors such as relative density of sand, embedment ratios, and various GFR parameters including size, number of layers, and the proximity of the layer to the symmetrical anchor plate were investigated in a scale model. The failure mechanism and the associated rupture surface were observed and evaluated. GFR, a tied up system made of fiber reinforcement polymer (FRP) strips and end balls, was connected to the geosynthetic material and anchored into the soil. Test results showed that using GFR reinforcement significantly improved the uplift capacity of anchor plates. It was found that the inclusion of one layer of GFR, which rested directly on the top of the anchor plate, was more effective in enhancing the anchor capacity itself than other methods. It was found that by including GFR the uplift response was improved by 29%. Multi layers of GFR proved more effective in enhancing the uplift capacity than a single GFR reinforcement. This is due to the additional anchorage provided by the GFR at each level of reinforcement. In general, the results show that the uplift capacity of symmetrical anchor plates in loose and dense sand can be significantly increased by the inclusion of GFR. It was also observed that the inclusion of GFR reduced the requirement for a large L/D ratio to achieve the required uplift capacity. The laboratory and numerical analysis results are found to be in agreement in terms of breakout factor and failure mechanism pattern.